(untitled) (Latakia University Journal -Medical Sciences Series, 2022)
Purpose: To evaluate the effect of pupil dilation using cyclopentolate hydrochloride 1%on ocular biometrics and intraocular lens power calculation using contact ultrasonography. Material and methods: In this cross sectional study, biometrics measurements were performed 80 eyes of patient with cataract scheduled for cataract surgery at the ophthalmology department of tishreen university hospital lattakia from June 2021 to June 2022 by using contact ultrasonography (AVISO Quantel). The axial length (AL), anterior chamber depth (ACD) mean keratometry (KM) and intraocular lens (IOL) power using SRK/T and Haigis formulas were measured before and after instillation of cyclopentolate hydrochloride 1% eye drop. Each parameter was compared by a paired T student prior to and after papillary dilation and the results were analyzed. Results: ACD increased by 3.61% and the difference was statistically significant (P=0.005). while the difference was not significant in AL before and after pupil dilation p=0.3 and Km (p=0.80). There is no affect of pupil dilation on Iol power calculation based on SRK/T formula targeting emmetropia (p=0.05).while using the Haigis formula significantly changed calculations for emmetropia p=0.008. Conclusion: pupil pharmaceutical dilation using cyclopentolate hydrochloride 1% significantly affect the ultrasonic measurements of ASCD and Iol power calculation using Haigis formula Keywords: pupil dilation – Axial length – anterior chamber depth – mean keratometry – Iol power contact ultrasonography – SRT/t formula – Haigis formula.